Changes in Plasma Metabolites Concentrations in Obese Dogs Supplemented With Anti-oxidant Compound - Kawasumi, Koh; Murai, Tae; Mizorogi, Takayuki; Okada, Yuki; Yamamoto, Ichiro; Suruga, Kohei; Kadokura, Kazunari; Arai, Toshiro (Frontiers in Nutrition, 2018)
The aim of this study is to discuss the effect of anti-oxidant supplement (Rv-PEM01-99, Kibun Foods, Inc., Tokyo, Japan) on changes in energy metabolism in obese dogs. 5 mg/ kg/day of Rv-PEM01-99 were applied for 6 weeks to the Beagle dogs fed high fat diet (HFD) or control diet (CD). In the present study, body weight (BW) decreasing effect of Rv-PEM 01-99 in dogs was not clear. However, at the end of experiment , plasma alkaline phosphatase (ALP) activities were significantly decreased and total cholesterol (TC), blood urea nitrogen (BUN) concentrations were decreased in HFD ＋Rv-PEM 01-99 group compared to those in HFD group. Plasma malondialdehyde (MDA) and triglycerides (TG) levels and lactate dehydrogenase (LDH) activities in CD＋Rv-PEM 01-99 group were significantly decreased compared to those in CD group. From these findings, Rv-PEM 01-99 seems to be not harmful for dogs. Anti-lipid peroxide effect and liver function improvement are expected in the dogs supplemented with Rv-PEM 01-99.